STUDY OF CONSUMER ACCEPTANCE OF CHOCOLATE BISCUITS CHOCO CHIPS WITH (Leptobarbus hoevenii) FISH FLOUR - Paramita, Cyntia; ', Edison; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The aim of this study was to determine the consumer acceptance of chocolate biscuits choco chips with addition Leptobarbus hoevenii fish flour About 6 kg Leptobarbus hoevenii obtained from Kampar market was processed into fish flour and chocolate biscuits choco chips was made. Four types of chocolate biscuits choco chips were made from fish flour, mocaf flour, dark chocolate, sugar, butter, milk powder, choco chips and each of treatment was added with 0%, 10%, 20%, and 30% of fish flour. Parameters was observed on consumers acceptance, proximat analysis and activity antiokxidant. The result showed that the chocolate biscuits choco chips added with 30% of Leptobarbus hoevenii fish flour was the best treatment and preferred by consumers with 3,14% of water, 0,42% of ash, 12,95% of protein, 21,56% of fat, 60,59% of carbohydrate and 11,43% of activity antiokxidant (IC50).Keywords: Leptobarbus hoevenii, chocolate biscuits, fish flour, consumers acceptance.